(untitled) (Anwer Khan Modern Medical College Journal, 2014)
A complete systematic investigation of unnatural death helps the court hugely to give an acceptable judgement. Legal officers like officer-in-charge of a police station, magistrates, witnesses of death circumstances and the forensic pathologists are basically involved in such investigation. Proper and true documentation by investigating officer are necessary. Identification of the deceased person, cause of death, manner of death, mode and mechanism of death, time since death, weapons used to cause the injuries etc. are opined in the investigaiton report as per direction given in the code of criminal procedure. These matters have been discussed in this article. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21130 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 34-38